Зачем телефону соты? - Богдарин Андрей Юрьевич (Почемучкины книжки, 2018)
Экземпляры: ДО мл.аб. (2022) / Инвентарный номер: 57811 / Цена: / Сис.шифр: 32.882 / Авт.знак: Б-73 / ГРНТИ: 49.39 / ББК: 32.882